Transitions of water‐drop impact behaviour on hydrophobic and hydrophilic particles. (11th January 2013) - Hamlett, C. A. E.; Atherton, S.; Shirtcliffe, N. J.; McHale, G.; Ahn, S.; Doerr, S. H.; Bryant, R.; Newton, M. I.
<x xml:space="preserve">Abstract</x> Extreme soil water repellency can have substantial implications for soil hydrology, plant growth and erosion, including enhanced splash erosion caused by raindrop impact. Previous studies of water droplet impact behaviour on man‐made super‐hydrophobic surfaces, with which water‐repellent soil shares similar characteristics, revealed three distinct modes of splash behaviour (rebound, pinning and fragmentation) distinguished by two transition velocities: rebound‐to‐pinning (vmin) and pinning‐to‐fragmentation (v*). By using high‐speed videography of single water droplet impacts we show that splash behaviour is influenced by the hydrophobicity of immobile particles, with hydrophobic glass spheres exhibiting all three modes of splash behaviour in the hydrophobic state but hydrophilic spheres exhibiting solely pinning behaviour. We found that increasing the particle size of fixed glass spheres increases vmin. A study of droplet impact on hydrophobic sand shows that the increased roughness of the immobile particles makes impacting droplets more likely to fragment at slower impact velocities. The mobility of the particles influenced droplet impact behaviour, with loose, hydrophobic particles displaying significantly greater vmin values than their fixed analogues. The surface tension of the water droplet also lifted loose, hydrophobic particles from the surface, forming highly mobile 'liquid marbles'. Water‐repellent soil was also shown to form 'liquid marbles' at both the slow (approximately 0.3–2.1 m s−1) and fast (about 7 m s−1) droplet impact velocities studied. The observation of very mobile liquid marbles upon water droplet impact on water‐repellent soil is significant as this provided a mechanism that may enhance erosion rates of water‐repellent soil.